How to connect the brand to the customer - Michon, Richard (Henry Stewart Talks, 2009)
From differentiation to positioning to branding, Branding of tangible products and intangible services, Branding and the promise made to customers, The brand in the customer's mind, Brand positioning process, Differentiated value proposition, Implementation is the key, Leadership and corporate culture